Shack-hartmann wavefront sensor with holographic lenslet array for the aberration measurements in a speckle field - Podanchuk, D.V.; Kurashov, V.N.; Dan’ko, V.P.; Kotov, M.M.; Sutyagina, N.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The application of a Shack-Hartmann sensor with holographic lenslet array to the measurements of wavefront aberrations in a speckle field is offered. The main feature of the method is that the tested wave front can be compared with an arbitrary wavefront preliminary recorded in the holographic memory of the array. An iterative algorithm of the sensor work for measuring the variable speckled wavefronts is offered. The experimental results of measurements of the curvature of a spherical speckled wave are presented. The possibility to use the method proposed in the analysis of deformations of a rough surface is shown.